Tooth Loss Suppresses Hippocampal Neurogenesis and Leads to Cognitive Dysfunction in Juvenile Sprague–Dawley Rats - Hu, Jiangqi; Wang, Xiaoyu; Kong, Wei; Jiang, Qingsong (Frontiers in Neuroscience, 2022)
Background: Both animal studies and prospective observational studies on patients with neurodegenerative disease have reported a positive link between oral diseases and cognitive function. However, the effect of early tooth loss on hippocampal morphology remains unknown. Methods: In this study, 6-week-old, male, juvenile Sprague–Dawley (SD) rats were randomized into the control (C) and tooth loss (TL) groups. In the TL group, all right maxillary molars of SD rats were extracted, while in the C group, no teeth were extracted. After 3 months, the learning and memory behavior were examined by Morris Water Maze (MWM), and the protein expression and mechanic signaling pathways were analyzed by real-time polymerase chain reaction, and cresyl violet staining. Results: Two days after the operation, the body weight of both groups recovered and gradually returned to the level before operation. Three months after tooth extraction, the completion time of the C group in the MWM was significantly shorter than the TL group. The mRNA expression of BDNF, TrkB, AKT1, and NR2B in the C group were significantly higher than in the TL group; The pyramidal neurons in the TL group was fewer than in the C group. Conclusion: Tooth loss in the juvenile SD rats will reduce the number of pyramidal neurons in the hippocampus, inhibit the expression of BDNF, TrkB, AKT1, and NR2B, and eventually lead to cognitive dysfunction.